Repair of furcal perforation with Biodentine follow-up of 14 months - Calero Hinostroza, Gisella Gaby (2020)
During the root canal treatment procedure, complications such as perforations at different levels may occur, the most common being furcal perforation associated with the cameral opening. However, the bioceramic cements currently available can provide better outcomes. We present a case of a right lower first molar with furcation, which was sealed with Biodentine®.